Stability of lower limit of air pressure in abandoned coal mine roadways during long-term CAES - Jiang, Jian; Guo, Pengyu; Yu, Xiaokui; Lin, Qili; Li, ZhiGuo; Wu, Jitao; Wu, Jianxun (Frontiers in Ecology and Evolution, 2023)
Power supply instability in the grid has been exacerbated by the rapid development of new energy generation methods. Notably, large-scale energy storage is the most practical solution to this problem. Meanwhile, in China, an effective method of reusing the increasing number of abandoned coal mines is urgently required. Accordingly, building compressed air energy storage (CAES) plants along the roadways of abandoned coal mines can serve as a viable energy storage method while repurposing these mines. This study examined the effect of the lower limit of air pressure (LLAP) on the stability of coal mine roadways in CAES applications by considering an ongoing pilot CAES coal mine in Chongqing, China. The findings indicate that the LLAP has a positive correlation with the roadway stability provided the frequency of air injection/extraction and upper limit of air pressure are constant. Over 10 years of CAES operation, a higher LLAP corresponds to less overall deformation of the roadway and top slab subsidence, and smaller plastic zone volume. Furthermore, the first main principle stress also decreases as the LLAP increases. According to the findings of this paper, the LLAP for the actual operation of CAES should be adjusted upwards as appropriate, which help to improve the geological stability of CAES roadways.